Straining effects in MoS2 monolayer on nanostructured substrates: temperature-dependent photoluminescence and exciton dynamics. Issue 12 (14th March 2018) - Hu, Yaowu; Zhang, Feng; Titze, Michael; Deng, Biwei; Li, Hebin; Cheng, Gary J.
Abstract : Strain-engineering of two-dimensional (2D) transition metal dichalcogenides (TMDs) has great potential to alter their electronic and optical properties. Abstract : Strain-engineering of two-dimensional (2D) transition metal dichalcogenides (TMDs) has great potential to alter their electronic and optical properties. Thus far, experimental studies of the straining effects in 2D TMDs primarily focused on the static property measurements at room temperature. However, low-temperature and temperature-dependence studies are essential in understanding the underlying mechanisms of the unique properties of monolayer TMDs. Herein, the temperature-dependent dynamic properties of laser shock strain-engineered monolayer MoS2 were studied using temperature-dependent photoluminescence (PL) and pump–probe spectroscopy. Both the photoluminescence spectra and exciton dynamics exhibit the differences between the MoS2 monolayers transferred on the flat and nanostructured surfaces by laser shock strain engineering and display a strong temperature dependence. The laser-induced straining effect and temperature-dependent dynamic behavior of MoS2 were studied through molecular dynamics simulation. The observed behaviors can be explained by the thermally induced strain in the monolayer MoS2 due to the mismatching thermal expansion coefficients of the monolayer and the substrate, which are coupled by the van der Waals forces. The ultrafast pump–probe experiments were performed to investigate the effect of strain on the exciton dynamics upon optical excitation. The results from the pump–probe measurements indicate that the effects of strain extend beyond that of the static properties and profoundly influence the valley carrier dynamics. This report extends the understanding of the substrate-induced straining effect to temperature-dependent luminescence behaviors and dynamic behaviors of the TMD materials.